Forming methodology and mechanism of a novel sheet metal forming technology - electromagnetic superposed forming (EMSF). (15th October 2018) - Long, Anlin; Wan, Min; Wang, Wenping; Wu, Xiangdong; Cui, Xuexi; Ma, Bolin
Highlights: A novel forming technology for large-scale sheet metals is proposed. Mechanism is based on superposition of local deformations after spring-back. Relative magnitude of local deformation determines bending direction of specimen. Specimen should be 2D curved in case of using a flat punch matrix. Abstract: This work is aimed at introducing a novel technology for forming large-scale and small-curvature aluminum alloy sheet using pulsed electromagnetic force. This method is named electromagnetic superposed forming (EMSF). Two basic experiments are carried out to demonstrate practical methodology of this newly proposed method. The electromagnetic force is applied on a sheet that is placed above a punch matrix. It results in local shallow dome-shaped and/or bowl-shaped plastic deformations according to spherical ends of punches and spaces between the punches. Positioning the coil and punch matrix along sheet surface incrementally, a uniformly distributed deformation matrix is generated. Two doubly curved specimens are obtained. One specimen bends towards the punch whereas the other bends towards the coil. Based on bending theory of thin plate, forming mechanism of this method is carried out using analytical analyses and numerical simulations. The results show that final macroscopic deformation of the sheet depends on superposition of those local plastic deformations. The relative magnitude of spherical radius which is between local dome-shaped deformation and bowl-shaped deformation determines macroscopic bending direction of specimen. In other words, small radius leads to high plastic deformation and bending direction of the specimen is in accordance with local deformation with small bending radius. Graphical abstract: